2021
DOI: 10.3390/ijms22083975
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Astrocyte Transcriptional Signatures in Response to Neuroactive Compounds

Abstract: Astrocytes play central roles in normal brain function and are critical components of synaptic networks that oversee behavioral outputs. Despite their close affiliation with neurons, how neuronal-derived signals influence astrocyte function at the gene expression level remains poorly characterized, largely due to difficulties associated with dissecting neuron- versus astrocyte-specific effects. Here, we use an in vitro system of stem cell-derived astrocytes to identify gene expression profiles in astrocytes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…Interestingly, one signature transcript that was not significantly different, SLC1A2 (which encodes the glutamate transporter 1 protein, GLT-1), was not restricted in iAstros potentially due to moderate expression in neurons. This correlates with our previous findings that the SLC1A2 transcript and/or protein is highly increased in hPSC-derived astrocytes ( Krencik et al, 2017b ) and mouse embryonic stem cell–derived astrocytes ( Sardar et al, 2021 ) when cocultured in the presence of iNeurons, which brings to light the importance of the external environmental signals in modeling bona fide functional astrocytes. Altogether, these resources provide valuable insight into the major distinctions between cell subtypes and further validate the transdifferentiation approach.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, one signature transcript that was not significantly different, SLC1A2 (which encodes the glutamate transporter 1 protein, GLT-1), was not restricted in iAstros potentially due to moderate expression in neurons. This correlates with our previous findings that the SLC1A2 transcript and/or protein is highly increased in hPSC-derived astrocytes ( Krencik et al, 2017b ) and mouse embryonic stem cell–derived astrocytes ( Sardar et al, 2021 ) when cocultured in the presence of iNeurons, which brings to light the importance of the external environmental signals in modeling bona fide functional astrocytes. Altogether, these resources provide valuable insight into the major distinctions between cell subtypes and further validate the transdifferentiation approach.…”
Section: Resultssupporting
confidence: 91%
“…One primary experimental approach designed to define human astrocyte reactivity in vitro consists of proinflammatory protein treatment to monocultures, followed by coculture with neurons ( Table S1 ); however, the consequence of selective stimulation of astrocytes within established human neural networks is yet to be detailed. It is known that the presence of neurons and neuron-derived intercellular signaling molecules activates intracellular pathways of astrocytes and elicits functional changes ( Sardar et al, 2021 ; Hasel et al, 2017 ). An emerging technology for cell-specific activation to mimic neurotransmitter signaling from neurons or drug responsiveness within multicellular models is chemogenetic-mediated G protein–coupled receptor (GPCR) signaling pathway stimulation ( Hirbec et al, 2020 ; Yu et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…3F) could explain the observed differences in closing wound gaps in AGES, as they are crucial for a rapid cell-cell contact remodeling during wounding 29,30 . Underling our ndings, PCA analysis using published transcriptomic data of other murine stem-cell derived astrocytes 31 revealed a clear separation from neonatal and adult primary astrocytes indicating major gene expression changes between primary and stem cell-derived cells (Fig. S3E).…”
Section: Resultssupporting
confidence: 62%
“…Recent studies shown that neurons and neuron-derived neuroactive compounds influence the development and function of astrocytes by regulating their gene expression. 49,50 Therefore, we propose that the interaction between hscNPCs and hscAS might be critical for SCI repair.…”
Section: Discussionmentioning
confidence: 99%